(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
This paper aims to analyze the end-of-life regulation in the Swiss legal system in order to understand the phenomenon of suicide tourism from Italy to Switzerland. First, the Author focuses on the analysis of the Swiss regulatory sources, both at the federal and cantonal level, and of the supranational and federal case-law. Secondly, the novelties in the Italian panorama are examined. Finally, the Author focuses on the phenomenon that connects the two systems: suicide tourism, that has also spread due to the activity carried out by suicide assistance associations.